Novel Dengan Ilustrasi Mengenai Permainan Tradisional Bola Leungeun Seuneu (Boles) - Faridah, Haifa RR; Ekawardhani, Yully Ambarsih (DIVAGATRA - Jurnal Penelitian Mahasiswa Desain, 2021)
Bola leungeun seuneu called boles is a traditional game originating from Sukabumi. Widely known during the Padjajaran Kingdom, making it a cultural heritage from the ancestors of the Sundanese land. Many consider this game extreme, in fact this game is safe for children to adults. This happens because of the lack of information regarding the bola leungeun seuneu. In the design that was made, information about this game will be made in the form of a novel that is packaged lightly through the novel with illustration media. Contains functional and philosophical aspects of traditional leungeun ball games such as how to play, rules of play, the benefits of the game, how to make balls, and so forth. This design is aimed at mid teens. With the information on the traditional leungeun seuneu (boles) ball game, the knowledge of culture will increase, especially regarding the bola eungeun seuneu (boles) ball game. As well as book readers who are targeted at mid teens, they understand the value of the concept of the leungeun seuneu (boles) ball game both functionally and with the benefits and philosophy contained therein.